Pemanfaatan Daun Jati Sebagai Zat Pewarna Coklat Pada Cat Bodypainting - Sofia Daniati; Raizki Anti Dwitiyaning Pangestu Mukhlisin Saputra (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Teak is a plant that produces attractive red and brown colors besides that it has many useful ingredients, so it is used as a natural dye. Researchers use teak leaves as a coloring agent in bodypainting. The purpose of this research is to create the use of teal leaves as a brown coloring agent in bodypaiting paint. The method used is the observation method, the library method, tehe experimental method, the documentation method, and the questionnaire method. Based on the feasibility test of the bodypainting product, it was found that the average score on the resulting color assessment inicator was 8,6 including the fairly decent category. On the texture assessment indicator, which is 8 and is included in the fairly decent category. On the aroma assessment indicator that is 7,3. And included in the category less feasible. Meanwhile, based on the results of the public test, it was found that te average score on the resulting color sharpness assessment indicator was 4, which was included in the proper category. In the humidity assessent indicator 4,2 is included in the very feasible category. In the indicator of coloring resistance assessment, with an average of 3 it is included in the category of quite decent enough. In the assessment inicator og the ease of removing bodypainting, which wa found with a score of 4,8 it was included in the very feasible category. The conclusion of this study is that the dye in teak leaves can be used as a natural dye in the manufacture of bodypainting. The best suggestion in this research is to add the aroma of bodypainting with essential oil in oerder to produce a fragrant aroma and for the packaging it must have a high appeal to the public. Further research is needed to determine the expiration date and color resistance of beetroot dyes.